Decoding stratigraphic and structural evolution of the Songliao Basin: Implications for late Mesozoic tectonics in NE China. (1st June 2020) - Zhu, Jichang; Feng, Youliang; Meng, Qing-ren; Li, Shihu; Wu, Guoli; Zhu, Rixiang
Graphical abstract: Geological interpretation profile of BB′ in Fig. 2. Highlights: The Yanshanian orogeny resulted from subduction of the Paleo-Pacific Ocean plate. The boundary of symmetrical sagging and asymmetrical sagging is T07 . The true meaning of the angle unconformity T5 is the Paleo-Asian Ocean orogeny. Abstract: An analysis of the structural styles and sedimentary filling of the Songliao Basin (SB) in the late Mesozoic was carried out based on a detailed interpretation of a large number of 2D and 3D seismic reflection profiles. Using precise stratigraphic chronology, it was established that the SB mainly experienced five stages of evolution in the late Mesozoic, including thermal uplifting in the Late Jurassic, rifting in the Early Cretaceous, symmetrical subsidence early in the early Late Cretaceous, asymmetrical subsidence in the middle Late Cretaceous, and inversion at the end of Cretaceous. The structures contained listric faults and planar domino-style normal faults in the rifting stage; dense normal faults with small throw, as well as negative flower structures in the symmetrical subsidence stage; positive flower structures in the asymmetrical stage; and compression and inversion structures (e.g., angled unconformities and folds) in the inversion stage. Two angular unconformities identified in this area, T5 and T02, may reflect orogenic events caused by Paleo-Asian Ocean closure and subduction of the Paleo-Pacific Ocean Plate beneath northeastern Asia from SE to NW. The compressive stress of the Yanshanian orogeny in the Yanshan tectonic belt originated from the subduction of the Paleo-Pacific Ocean Plate rather than the closure of the Mongol-Okhotsk Ocean. Although the SB had already been influenced by Paleo-Pacific Ocean Plate subduction in the middle Late Cretaceous, the stress did not cause the inversion of the SB. The SB was affected by Paleo-Pacific Ocean Plate subduction during the deposition of the second member of the Nenjiang Formation in the Upper Cretaceous; however, significant orogenic events and obvious inversion of the SB did not take place until the end of the Late Cretaceous.